Denpasar Festival: A Sustainable Cultural Festival as a Reflection of Denpasar as a Creative City - Laksmi, Luh Putu Gita; Lestari, Qatrunnada; Ali, Moh; Masrur Maulidy, Ahmad; Suharto, Bambang (Lingual Journal of Language and Culture; Vol 16 No 2 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v16.i02.p07, 2023)
A program called "Sightseeing Denpasar" was formed to accommodate various arts and cultural activities, and also to develop tourism in the city of Denpasar. One of its signature activities is called Denpasar Festival. This article focused on examining the role of Denpasar Festival as a sustainable cultural festival to reflect Denpasar as a creative city. The method used is a literature study using journals related to Denpasar festival, sustainable festival and creative city.The results of this study showed that Denpasar Festival plays a significant role in the development and preservation of culture and tourism in Denpasar City. The application of Tri Hita Karana values is a good guideline for Denpasar Festival to become a sustainable festival. Reflecting on the Denpasar Festival, Denpasar City has great potential to become a culture-based creative city. Moreover, Denpasar has a historical and cultural background, as well as creative human resources, so Denpasar City is very capable of fulfilling the criteria for Creative City development.